2021
DOI: 10.1111/pce.14232
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism‐mediated mechanisms underpin the differential stomatal speediness regulation among ferns and angiosperms

Abstract: Recent results suggest that metabolism‐mediated stomatal closure mechanisms are important to regulate differentially the stomatal speediness between ferns and angiosperms. However, evidence directly linking mesophyll metabolism and the slower stomatal conductance (gs) in ferns is missing. Here, we investigated the effect of exogenous application of abscisic acid (ABA), sucrose and mannitol on stomatal kinetics and carried out a metabolic fingerprinting analysis of ferns and angiosperms leaves harvested through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 96 publications
2
8
0
Order By: Relevance
“…4B ), which mimicked the effects of drought stress. Our finding is consistent with the previous study that suggested the fast stomatal closure requires a high ABA sensitivity ( Candido-Sobrinho et al 2022 ). Our results also implied that ZmGLKs may function in the ABA biosynthesis pathway, as indicated by the higher ABA accumulation ( Supplemental Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…4B ), which mimicked the effects of drought stress. Our finding is consistent with the previous study that suggested the fast stomatal closure requires a high ABA sensitivity ( Candido-Sobrinho et al 2022 ). Our results also implied that ZmGLKs may function in the ABA biosynthesis pathway, as indicated by the higher ABA accumulation ( Supplemental Fig.…”
Section: Discussionsupporting
confidence: 94%
“…This has been demonstrated by model simulations and experimental data that major C 4 crops are capable of more rapid stomatal closure compared to C 3 crops in response to water deficit, resulting in the high water use efficiency (WUE) ( McAusland et al 2016 ; Wang et al 2021 ; Ozeki et al 2022 ). Notably, previous studies have demonstrated that slower stomatal closure in ferns is associated with reduced responsiveness to ABA and sugars compared to angiosperms ( Lima et al 2019 ; Candido-Sobrinho et al 2022 ), while the rapid transport of ions and osmolytes between guard cells and subsidiary cells in grass species contributes to the fast stomatal movement ( Chen et al 2017 ). Rice plants overexpressing ZmGLK s have improved carbohydrate contents ( Li et al 2020 ), consistent with SlGLK gene expression in tomato plants ( Powell et al 2012 ; Nguyen et al 2014 ); this may contribute to rapid stomatal closure at the metabolic level.…”
Section: Discussionmentioning
confidence: 99%
“…1b; see also details in the Materials and Methods section). In line with previous studies on mature ferns (Hõrak et al, 2017;Xiong & Flexas, 2020;Cândido-Sobrinho et al, 2022), stomatal conductance (g s ) and net photosynthesis rate (A net ) in juvenile ferns were generally low (Fig. 1c,d).…”
mentioning
confidence: 52%
“…2c,e,g,h,j). This might explain why no ABA responses were previously found in shorter experiments (Cândido-Sobrinho et al, 2022).…”
mentioning
confidence: 70%
“…1b; see also details in Materials and Methods). In line with previous studies on mature ferns (Hõrak et al ., 2017; Xiong & Flexas, 2020; Cândido-Sobrinho et al ., 2022), stomatal conductance ( g s ) and net photosynthesis rate ( A net ) in juvenile ferns were generally low (Fig. 1c, d,).…”
Section: Main Textmentioning
confidence: 99%